Analysis of an in vivo model to study the interaction of host factors with Candida albicans. - Poor, A H (1981)
Conditions were established under which membrane diffusion chambers surgically implanted into mice could be used to study interactions between host defense factors and Candida albicans within the chambers. Depending on the size of membrane pores, soluble host substances and phagocytic cells entered the chambers during the first 24 h after chamber implantation. By 7 days in vivo, the membranes of chambers appeared impermeable to these host factors. Mouse phagocytic cells were found to be functional within the in vivo chambers whether the cells emigrated to the chambers on their own accord or were placed there before chamber implantation. Opsonic factors such as antibody and complement appeared to be biologically functional within the in vivo chambers. Conditions suitable for harvesting C. albicans from the chambers also were determined.